BATHYMETRIC SURVEY OF WATER PARAISO, SAO FRANCISCO, PARAIBA, BRAZIL - Guimarães, Carlos Lamarque; Ribeiro, George do Nascimento; Vieira, Lucílio José de Santos (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2009)
The objective main this work has the shows the results of the bathymetric survey done in automated of the lake Paraiso (São Francisco municipality, Paraiba state), in the month of december 2005, as well present its stored water bulk calculated from the survey, water’ mirror and develop the new quota vs area vs water bulk.